Correlation between Knowledge and Attitude towards Compliance with Antidiabetic Use in Type 2 Diabetes Mellitus Patients at RS X - Siswati, Siswati (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. The increasing prevalence of diabetes due to lack of knowledge that affects the attitude of patients so that they are not compliant in carrying out treatment. The aim of the study was to determine whether there is a relationship between knowledge and attitudes towards adherence to the use of antidiabetics in type 2 diabetes mellitus patients at Hospital X. The method used is descriptive analytic with cross sectional design. The population and research sample were 110 respondents using purposive sampling technique. The research instruments used were the knowledge questionnaire (DKQ-24), the attitude questionnaire and the compliance questionnaire (MMAS-8). The results showed that 15 people (13.6%) had good knowledge, 55 people (50.0%) had sufficient knowledge, and 40 people (36.4%) had less knowledge. Attitudes of type 2 diabetes mellitus patients were 72 people (65.5%) who had a positive (good) attitude and 38 people (34.5%) had a negative (bad) attitude. For compliance with the use of antidiabetics, 18 people (16.4%) had high adherence, 38 people (34.5%) had moderate adherence and 54 people (49.1%) had low adherence. The results of the Chi square statistical test showed a significant relationship between knowledge and compliance with a value of ρ=0.019 (ρ<0.05), and there was also a significant relationship between attitudes and compliance with a value of ρ=0.044 (ρ<0.05).